SAT0324 ABCG2 Dysfunction Leads to Renal Urate Underexcretion Type Hyperuricemia in Addition to Extra-Renal Urate Underexcretion Type Hyperuricemia. (9th June 2015) - Ichida, K.; Matsuo, H.; Nakayama, A.; Sakiyama, M.; Chiba, T.; Shimizu, S.; Nakashima, H.; Nakamura, T.; Takada, Y.; Takada, T.; Nakaoka, H.; Wakai, K.; et al.
Abstract : Background: Hyperuricemia induces common diseases, gout and kidney stones, and accelerates the progression of renal diseases. Hyperuricemia has been clinically classified into the urate overproduction type (the renal urate overload type) including the extra-renal urate underexcretion type, the renal underexcretion type, and the combined type. We have reported that the dysfunction of ATP-binding cassette transporter, sub-family G, member 2 (ABCG2) is the major cause of hyperuricemia, especially extra-renal urate underexcretion type hyperuricemia. But its involvement in renal underexcretion type hyperuricemia, the most prevalent subtype, is not clearly explained so far. Objectives: The aim of present study is to determine the contribution of ABCG2 to the onset of each type of hyperuricemia. Methods: We performed the association analysis with hyperuricemia patients and controls in male Japanese. Results: ABCG2 dysfunction significantly increased the risk of the whole hyperuricemia and renal urate overload type hyperuricemia, according to the severity of impairment. Furthermore, slight and moderate ABCG2 dysfunction significantly increased the risk of renal underexcretion type hyperuricemia. ABCG2 dysfunction caused renal urate underexcretion and induced hyperuricemia even if the renal urate overload was not remarkable. Conclusions: These results show that ABCG2 plays physiologically important roles in both renal and extra-renal urate excretion mechanisms. References: Matsuo H, Takada T, Ichida K, et al: Common defects of ABCG2, a high-capacity urate exporter, cause gout: a function-based genetic analysis in a Japanese population. Sci Transl Med 1:5ra11, 2009 Ichida K, Matsuo H, Takada T, et al: Decreased extra-renal urate excretion is a common cause of hyperuricemia. Nat Commun 3:764, 2012 Matsuo H, Nakayama A, Sakiyama M, et al: ABCG2 dysfunction causes hyperuricemia due to both renal urate underexcretion and renal urate overload. Sci Rep 4:3755, 2014 Disclosure of Interest: None declared